1996
DOI: 10.1172/jci118596
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic carboxyl ester lipase: a circulating enzyme that modifies normal and oxidized lipoproteins in vitro.

Abstract: Pancreatic carboxyl ester lipase (CEL) hydrolyzes cholesteryl esters (CE), triglycerides (TG), and lysophospholipids, with CE and TG hydrolysis stimulated by cholate. Originally thought to be confined to the gastrointestinal system, CEL has been reported in the plasma of humans and other mammals, implying its potential in vivo to modify lipids associated with LDL, HDL (CE, TG), and oxidized LDL (lysophosphatidylcholine, lysoPC). We measured the concentration of CEL in human plasma as 1.2 Ϯ 0.5 ng/ml (in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 59 publications
5
93
0
Order By: Relevance
“…Results showing the presence of the cholesterol esterase in human aorta (17), and its increased secretion by oxidized LDL-stimulated human macrophages (Fig. 3), suggested its possible role in atherogenesis.…”
Section: Expression Of Cholesteryl Ester Hydrolytic Enzymes In Mousementioning
confidence: 87%
See 3 more Smart Citations
“…Results showing the presence of the cholesterol esterase in human aorta (17), and its increased secretion by oxidized LDL-stimulated human macrophages (Fig. 3), suggested its possible role in atherogenesis.…”
Section: Expression Of Cholesteryl Ester Hydrolytic Enzymes In Mousementioning
confidence: 87%
“…The mRNA for bile salt-stimulated cholesterol esterase was also present in human eosinophils (42). Bile salt-stimulated cholesterol esterase activity, which could be inhibited by antibodies specific for the pancreatic enzyme, was also reported to be present in human serum and in the aorta (16,17). These results suggested that bile saltstimulated cholesterol esterase may have a systemic origin and participates in systemic lipid metabolism, in addition to its role for nutrient digestion and transport in the gastrointestinal tract (43).…”
Section: Expression Of Cholesteryl Ester Hydrolytic Enzymes In Mousementioning
confidence: 91%
See 2 more Smart Citations
“…BSDL is synthesized to a limited extent by human-monocytes-macrophages (32), endothelial cells (33,34), eosinophils (35), and the liver (22,36,37). BSDL has also been localized in necrotic areas of the pancreas, consecutive to an acute pancreatitis (38).…”
Section: Discussionmentioning
confidence: 99%